Anatomical Profile and Morphometric Evaluation of Human Sacral Hiatus in North Indians - Renu Chauhan,; Mahindra Nagar, (Faculty of Medicine, UKM Medical Centre, 2015)
Successful caudal epidural block (CEB) for various gynaecological and orthopaedic procedures requires an elaborate knowledge of anatomical profile of sacral hiatus. Varied morphology of sacral hiatus is likely to influence the success rate of CEB. Scanty literature is available on the morphometry of sacral hiatus in North Indian subjects. Therefore, sacral hiatus of 60 North Indian human sacra were evaluated using Vernier calipers. Sexing of the sacra was done by calculating the sacral index. Following parameters of sacral hiatus were observed and recorded: a) Shape, b) Level of apex, c) Maximum distance between the sacral cornua, d) Length of the sacral hiatus i.e. from its apex to midpoint of its base, e) Antero-Posterior diameter at the apex of sacral hiatus. The data obtained was analyzed using SPSS software (version 18). Various shapes of sacral hiatus were observed. It was irregularly shaped in both the sexes though inverted U shaped sacral hiatus was also seen frequently in females. In males, the apex of sacral hiatus was commonly seen at the level of spinous process of 3rd sacral vertebra in males and below the level of spinous process of 4th sacral vertebra in females. The mean distance between the sacral cornua was 1.1cm : 1.2cm in males and females, respectively. Mean length of the sacral hiatus was 2cm in both sexes. Antero-posterior depth at the apex the sacral hiatus was 6mm in both the genders. The dimensions of sacral hiatus obtained in this study were inconsistent with earlier studies. Knowledge of these dimensions may help the clinicians in precisely locating sacral hiatus for successful CEB in North Indians.